Combination Drug Therapy for Pain following Chronic Spinal Cord Injury. (18th March 2012) - Hama, Aldric; Sagen, Jacqueline
Abstract : A number of mechanisms have been elucidated that maintain neuropathic pain due to spinal cord injury (SCI). While target-based therapeutics are being developed based on elucidation of these mechanisms, treatment for neuropathic SCI pain has not been entirely satisfactory due in part to the significant convergence of neurological and inflammatory processes that maintain the neuropathic pain state. Thus, a combination drug treatment strategy, wherein several pain-related mechanism are simultaneously engaged, could be more efficacious than treatment against individual mechanisms alone. Also, by engaging several targets at once, it may be possible to reduce the doses of the individual drugs, thereby minimizing the potential for adverse side effects. Positive preclinical and clinical studies have demonstrated improved efficacy of combination drug treatment over single drug treatment in neuropathic pain of peripheral origin, and perhaps such combinations could be utilized for neuropathic SCI pain. At the same time, there are mechanisms that distinguish SCI from peripheral neuropathic pain, so novel combination therapies will be needed.